John Nietner collection of Sri Lankan Scydmaeninae (Coleoptera, Staphylinidae) - Jałoszyński, Paweł (Zootaxa, 2025)
The Scydmaeninae collection of John Nietner was rediscovered in the Museum and Institute of Zoology, Polish Academy of Sciences, Warsaw. The placement of each species is verified, all species are redescribed, and for each a lectotype is designated. Cephennodes ovatus (Nietner) is placed in the subgenus Aculeodes, Scydmaenus graminicola Nietner, treated by Csiki as Microscydmus, is placed in Euconnus (s. str.); Scydmaenus pyriformis Nietner, placed by Csiki in Microscydmus, is placed in Euconnus (s. str.); Scydmaenus ceylanicus Nietner is placed in Euconnus (incertae sedis); Scydmaenus femoralis Nietner is placed in the subgenus Mascarensia; Scydmaenus alatus is placed as incertae sedis within Scydmaenus. The type series of Scydmaenus pselaphoides Nietner is composed of three species that differ mainly in the male genital features; two of them can be identical with S. mantcioranus sensu Lhoste (= S. minangkabauensis sensu Franz) or S. hoabinhensis Lhoste. Status of these names, how many species hide behind them, and where they are distributed is unclear, because previous authors made identifications of specimens and synonymized some names without studying the type material and the available illustrations of aedeagi seem to contradict taxonomic and nomenclatural actions taken. It was found that Franz in his 1982 Sri Lankan monograph misidentified Scydmaenus femoralis, S. alatus, and S. pselaphoides, and that beetles from the Schaufuss collection he used for redescriptions were not type specimens. Results of examination of Nietner’s specimens affect also other species, and the following actions are taken: Cephennodes vegrandis Stevanović is transferred from Cephennodes (s. str.) to Aculeodes, and the diagnosis of Aculeodes is emended; Cephennodes breviusculus (Motschulsky) is removed from synonymy with Cephennodes ovatus (Nietner); Cephennodes ovatus Jałoszyński, a secondary junior homonym of Cephennodes ovatus (Nietner), is replaced with Cephennodes ovatides nom. nov.; Scydmaenus singaporanus Franz syn. nov. is placed as a junior synonym of Scydmaenus pselaphoides Nietner; Euconnus graminicola Franz, a secondary junior homonym of E. graminicola (Nietner), is replaced with Euconnus graminicolides nom. nov.; Euconnus quinquefoveolatus (Motschulsky) syn. nov. is placed as a junior synonym of Euconnus advolans (Nietner); Euconnus nocturnilankanus Jałoszyński syn. nov. (a replacement name for Euconnus nocturnus Franz, 1982, nec Franz, 1958) is placed as a junior synonym of Euconnus pubescens (Nietner); Euconnus brunnipennis (Motschulsky) and E. pyriformis (Nietner) are removed from synonymy with Euconnus intrusus Schaum; and Euconnus brunnipennis (Motschulsky) is placed in the nominotypical subgenus.